2012
DOI: 10.1039/c2pp05336e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet radiation and nutrients on the structure-function of phytoplankton in a high mountain lake

Abstract: The combined effect of high solar ultraviolet radiation (UVR) and nutrient supply in a phytoplankton community of a high mountain lake is analyzed in a in situ experiment for 6 days with 2 × 2 factorial design. Interactive UVR × nutrient effects on structural and functional variables (algal biomass, chlorophyll a (chl a), primary production (PP), maximal electron transport rate (ETR(max)), and alkaline phosphatase activity (APA)), as well as stoichiometric ones (sestonic N per cell and N:P ratio) were found. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 83 publications
5
23
0
Order By: Relevance
“…In the red alga Gracilaria lemaneiformis, UV-induced inhibition of photosynthesis and growth was exacerbated under P-limited conditions, but the presence of UVR enhanced the activity of total carbonic anhydrase in the thalli and raised the photosynthetic affinity for exogenous inorganic carbon (Xu & Gao 2009). In contrast, Carrillo et al (2008) and Korbee et al (2012) reported that addition of P to a high mountain lake resulted in enhanced UVR impacts.…”
Section: Nutrient−uvb Interactionsmentioning
confidence: 94%
“…In the red alga Gracilaria lemaneiformis, UV-induced inhibition of photosynthesis and growth was exacerbated under P-limited conditions, but the presence of UVR enhanced the activity of total carbonic anhydrase in the thalli and raised the photosynthetic affinity for exogenous inorganic carbon (Xu & Gao 2009). In contrast, Carrillo et al (2008) and Korbee et al (2012) reported that addition of P to a high mountain lake resulted in enhanced UVR impacts.…”
Section: Nutrient−uvb Interactionsmentioning
confidence: 94%
“…On the other hand, stratification traps phytoplankton populations in surface layers, increasing the light available for growth, but also exposing them to higher levels of ultraviolet radiation (UVR,. In this regard, it has been widely reported that greater exposure to UVR exerts an inhibitory effect on autotrophic and heterotrophic organisms (Häder et al, 2011), and that UV-B (280-315 nm), in particular, harms primary and bacterial production , enzymatic activity (Korbee et al, 2012), and cell viability , among other effects. However, it has been also reported Medina-Sánchez et al, 2002;) that UVR does not produce negative effects and it can even stimulate bacterial production and photosynthetic activity.…”
Section: P Carrillo Et Al: Synergistic Effects Of Uvr and Simulatedmentioning
confidence: 99%
“…It has also been demonstrated that UVR exposure in the upper layers of the water column can increase the proportion of photosynthate released as exudates (Carrillo et al, 2008;Korbee al., 2012), which would stimulate the growth of UVR-resistant bacteria (Xenopoulos and Schindler, 2003) and give rise to a coupled phytoplankton-bacteria relationship in clear oligotrophic lakes . Coupling between phytoplankton and bacterioplankton has been defined as the capacity of the carbon (C) released by phytoplankton to support the bacterial carbon requirement (Morán et al, 2002) and will therefore differ depending on (i) the availability of alternative (allochthonous or autochthonous) carbon sources (Gasol et al, 2009) and (ii) the supply of inorganic nutrients (Medina-Sánchez et al, 2010;López-Sandoval et al, 2011).…”
Section: P Carrillo Et Al: Synergistic Effects Of Uvr and Simulatedmentioning
confidence: 99%
“…Detailed investigations of the specificity of high mountain lakes is undertaken by various scientific disciplines (Choiński et al 2015). The research concerns both the biological (Korbee et al 2012;Kosolapova 2012;Degefu and Shagerl 2015) as well as physical-chemical and physical and chemical aspects (Tanaka and Tominaga 1994;Rodríguez-Rodríguez et al 2004;Santolaria et al 2015).…”
Section: Introductionmentioning
confidence: 99%